(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This article analyzes the negative impact of communist ideology on literature, art, and spiritual culture in Uzbekistan in the 1970s and 1980s using the example of Surkhandarya region. Communist ideology restricted creative freedom, forcibly promoted socialist realism, suppressed national values, and used art and culture as an ideological tool. In addition, independent-thinking artists were oppressed, and historical figures and national heritage were ignored. During this period, literature and art were required to serve only Soviet ideology, which seriously hindered the development of national culture